RESEARCH ON THE QUALITY INDICATORS OF CURD PRODUCTS BASED ON PROTEIN-HERBAL CLOTS - Olena GREK (Stefan cel Mare University of Suceava, 2017)
The article presents the research of qualitative indicators of curd products with different nutritional ingredients based on protein-herbal clots. The effect of the number of Rumex juice and the duration of thermoacid processing on the process of precipitation of milk proteins was determined. It was established that the introduction of vegetative coagulant in the amount (9 ± 0.5)% at a temperature (93 ... 95) °C and endurance (3 ... 5) min - provides the optimal yield of protein-herbal clot taking into account restrictions according to organoleptic parameters. The effect of white sugar and apple pectin in fiber on the organoleptic, physico-chemical and rheological indicators curd products was investigated. The dietary fibers increase moisture-proof ability and effective viscosity of samples, and white sugar reduces these indexes due to dehydrating properties. The optimal option is to add to the protein-herbal bunch at the same time two components when mixing - white sugar and apple pectin in fiber in quantities of 15% and 2% respectively. Taking into account the influence of individual non-dairy ingredients - Rumex juice of white sugar and apple pectin in fiber on curd products, the performance of the finished product can purposefully be affected.